The therapeutic concept and analysis of the effect of hormone package therapy in brain dead organ donors - Xu, Guixing; Xu, Ping; Zheng, Donghua; Wei, Wanjia (International Surgery Journal, 2019)
Background: The present study aimed to assess the effect of hormone package therapy on hemodynamic stability in brain dead organ donors. Methods: In this study, patients were divided into two groups: one administered hormone package therapy, defined as simultaneous treatment with vasopressin, thyroxine and corticosteroids; and the other administered conventional therapy. Clinical findings and hemodynamic parameters were compared to analyze the effect of hormone package therapy on hemodynamic stability. Associations between hormone package therapy and hemodynamic variables were assessed by univariate and multivariate logistic regression analyses. Results: A total of 109 patients were included in the study. Based on time of enrollment, 54 and 55 patients received conventional and hormone package therapy, respectively, with 32 (59.3%) and 45 (81.8%), respectively, achieving hemodynamic stability. High-doses of a single vasoactive agent in the hormone package group better maintained hemodynamic stability and norepinephrine use compared to conventional treatment. Univariate and multivariate analyses showed that an abnormal suprasellar cistern, midline shift, low free T3, axillary temperature >36.5°C and central diabetes insipidus were associated with the effects of hormone package therapy. Conclusions: Hormone package therapy can help maintain hemodynamic stability in brain dead donors and reduce the use of vasoactive agents, thereby improving the quality of donated organs and the success rates of organ donations.